Upregulation of cognitive control networks in older adults’ speech comprehension - Erb, Julia; Obleser, Jonas (Frontiers in Systems Neuroscience, 2013)
Speech comprehension abilities decline with age and with age-related hearing loss, but it is unclear how this decline expresses in terms of central neural mechanisms. The current study examined neural speech processing in a group of older adults (aged 56–77, n=16, with varying degrees of sensorineural hearing loss), and compared them to a cohort of young adults (aged 22–31, n=30, self-reported normal hearing). In an fMRI experiment, listeners heard and repeated back degraded sentences (4-band vocoding, which preserves the temporal envelope of the acoustic signal, while substantially degrading spectral information). Behaviourally, older adults adapted to degraded speech at the same rate as young listeners, although their overall comprehension of degraded speech was lower. Neurally, both older and young adults relied on the left anterior insula for degraded more than clear speech perception. However, anterior insula engagement in older adults was dependent on hearing acuity. Young adults additionally employed the anterior cingulate cortex (ACC). Interestingly, this age group × degradation interaction was driven by a reduced dynamic range in older adults, who displayed elevated levels of ACC activity in both conditions, consistent with a persistent upregulation in cognitive control irrespective of task difficulty. For correct speech comprehension, older adults recruited the middle frontal gyrus in addition to a core speech comprehension network on which young adults relied, suggestive of a compensatory mechanism. Taken together, the results indicate that older adults increasingly recruit cognitive control networks, even under optimal listening conditions, at the expense of these systems’ dynamic range.